Cacao Agroforestry in Mahakam Ulu: Transformation Strategy from Traditional to Good Agricultural Practices and Smart Agroforestry System - Catur Budi Wiati; Eddy Mangopo Angi; Karmilasanti Karmilasanti; Murniati Murniati; Sri Suharti; Indra A.S.L.P. Putri; Aris Pudji Hadi; Muhammad Furkan; Belasius Anyeq; Krista Tala; Veronica Carolina; Awaluddin Aziz; et al. (Forest and Society)
The Dayak community in East Kalimantan is renowned for practicing traditional Agroforestry (AF) across generations. Meanwhile, despite the long-term introduction of cacao (Theobroma cacao) in 1996 as a potential commodity in the AF practice, its productivity still needs to be improved. This study aimed to analyze the challenges as well as develop strategies for adapting and transforming traditional AF practices into Smart Agroforestry (SAF) systems for cacao. The implementation of cacao SAF is anticipated to enhance cacao productivity, improve the welfare of local communities, and preserve the forest’s function as a crucial life support system for the Dayak Community in Mahakam Ulu (Mahulu) District. Data were collected through the Triangulation Method, using interviews of selected respondents with structured questionnaires, in-depth interviews with key informants, and focus group discussions to verify and validate the data. Additionally, participatory mapping was carried out on AF cacao pattern to identify the area and its cultivation technique. We also obtained secondary data from local government sources in East Kalimantan. Data were processed using qualitative descriptive analysis, gender, and SWOT analysis. The results showed that the development of cacao-based agroforestry in Mahulu District was carried out by applying the green economy concept and considering the potential for cacao marketing, socio-economic culture, gender, and traditional knowledge. However, further development efforts are needed to improve traditional cultivation towards SAF practices. This requires multi-stakeholder collaboration from the regional level, comprising farmers and village government to the central government. Several important factors should be considered for better management of cacao cultivation. These factors include intensifying input production to increase land productivity, assuring land ownership status, improving the quality of products, increasing access to capital, as well as strengthening local institutions for a more effective and efficient marketing process.